Mixed Micelle-mediated Cloud Point Extraction Coupled to Spectrophotometry for Fast Screening of Salbutamol in Wastewater, Pig Feed and Pork Samples - Jitlada Vichapong (Faculty of Science, Chiang Mai University, 2020)
Chiang Mai Journal of Science